2015
DOI: 10.14202/vetworld.2015.82-87
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of solar dried blood and the ruminal content and its effect on performance of Japanese quails

Abstract: Aim:The aim was to determine the chemical composition of solar dried blood and rumen content (DBRC) and further ascertain the concentration at which DBRC could be included in Japanese quail diets without any adverse effect on its performance.Materials and Methods:Feeding trial on the effect of DBRC on performance of Japanese quails was studied up to 5 weeks. 252 numbers of day old (Nandanam Type III breed) Japanese quails were purchased from Poultry Research Station, Madhavaram and divided into 7 batches (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Up to 18% sun-dried bovine blood-RD meal in the diet did not adversely affect growth performance parameters of broilers grown to 56 days of age (Yitbarek et al 2016). Mishra et al (2015) observed that replacing 30% of dietary soybean meal with sun-dried blood-RD maintained the performance of growing quails. Most studies on the feeding of blood and RD to poultry have employed sun-drying rather than heat processing as used in the present study.…”
Section: Growth Performancementioning
confidence: 84%
See 1 more Smart Citation
“…Up to 18% sun-dried bovine blood-RD meal in the diet did not adversely affect growth performance parameters of broilers grown to 56 days of age (Yitbarek et al 2016). Mishra et al (2015) observed that replacing 30% of dietary soybean meal with sun-dried blood-RD maintained the performance of growing quails. Most studies on the feeding of blood and RD to poultry have employed sun-drying rather than heat processing as used in the present study.…”
Section: Growth Performancementioning
confidence: 84%
“…Rumen digesta (RD, partially digested feed in the rumen) and blood are two important byproducts of ruminant slaughter, which remain underutilised in many parts of the world, posing disposal concerns (Al Mamun et al 2018). RD is an average source of protein but is high in fibre and low in energy (Mishra et al 2015;Bekele et al 2020) and may contain antinutritional factors associated with fodders consumed by the animal (Elfaki and Abdelatti 2016). Blood is a rich protein source high in lysine, methionine and cysteine (Prata and Sgarbieri 2008;Adeniji 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al [103] also reported that the inclusion of solar dried blood and the ruminal digesta at varying levels of 0%, 5%, 10%, 15%, 20%, 25% and 30% to replace soybean meal in Japanese quail diets resulted in higher weight gains compared to the control group.…”
Section: Quailmentioning
confidence: 99%
“…A mixture of blood and rumen content is a good source of feed ingredients in poultry ration, catfish ration, quail ration, lamb ration and cattle ration, which are significant with no adverse effects on animals [96,[99][100][101][102][103]. When a suitable processing method is adopted, it reduces the amount of microorganisms present in the dried rumen digesta and reduces environmental pollution to a minimum level [102,104,105].…”
Section: Utilization Of Blood and Dried Rumen Digesta As Feed Ingredientmentioning
confidence: 99%
“…In fact, the fifth quarter can serve as palatability enhancers for various pet foods, further supporting product acceptability, humanization, and " premiumization " (Mullen et al., 2017). Furthermore, several authors have reported the use of rumen digesta as feed ingredient for lamb (Osman & Elimam, 2015), rabbit (Dairo et al., 2005), chicken (Adeniji & Balogun, 2001; Yitbarek et al., 2016), goat (Mondal et al., 2013), cattle (Cherdthong et al., 2014), and Japanese quail (Mishra et al., 2015) with no harmful impact on growth performance of the animal.…”
Section: Current Utilization Of the Fifth Quartermentioning
confidence: 99%